Accelerating The Development Of The Halal Industry Through A Strategy To Strengthen Micro, Small And Medium Enterprises (MSMEs) - Inud Danis; Vinda Nur Hidayah (At-Tasharruf "Jurnal Kajian Ekonomi dan Bisnis Syariah", 2026)
The Halal Industry in East Java Province is the main focus in accelerating sharia-based economic development. In an effort to achieve this vision, the development strategy is focused on strengthening Micro, Small, and Medium Enterprises (MSMEs). Its clusters, which are superior, are the main foundation to achieve acceleration in halal product certification. These cluster programs not only support the development of halal products, but also contribute significantly to meeting the needs of the domestic market. In the midst of these efforts, East Java Province has designed a master plan that includes key strategies, such as strengthening the halal industry value chain from upstream to downstream. This plan, one of whose strategies is to build a halal industrial estate, is an important milestone in accelerating the development of the halal industry in this region